Women in science and technology employment - DREW, EILEEN PATRICIA (Goodbody, 2001)
Ireland continues to experience the fastest growth in GNP within the European Union, with average GNP increases of almost 8 per cent per annum over the period of the late 1990's. This has led to buoyancy in the Irish labour market with increasing employment in both the manufacturing and services sectors. Sectors such as IT, electronics and internationally traded services have grown substantially, as has the chemical industry. In parallel with foreign led industry, Irish-owned sectors such as engineering and consumer foods have also expanded both in terms of production and employment. Employment in industry accounted-for--22=per--cent-of-maleemployment and 14.2 per cent of female employment in 2000 (CSO. 2000). Women's employment continues to be based more heavily than male in the:service..sector and service occupations. All available trends indicate a continuing increase in demand for female labour and a tightening of labour market conditions. It is increasingly recognised that women can make a contribution to meeting existing and future labour shortages in Ireland (National Competitiveness Council 2000). The current economic situation provides an opportunity for women to participate in greater numbers while at the same time contributing to meeting industry's growing needs for more skill intensive labour. Below we examine some of the recent reports on skill shortages in the SET sector.
PUBLISHED
Keywords: Statistics